Moderating and mediating effect of micro-takaful and training activities between Islamic microfinance and micro-entrepreneurship: a case study of Yemen - Alrashedi, Mohammed Yahya; Mohammed, Mustafa Omar; Othman, Anwar Hasan Abdullah (2020)
Although Yemen has adopted policies and measures to develop micro-entrepreneurship as a tool to combat unemployment and help unemployed people create their micro-enterprises over the past 20 years, the micro-entrepreneurship is still facing critical challenges and the unemployment rate continues to increase significantly. The objective of the study is to examine the moderating and mediating effect of micro-takaful and training respectively between the Islamic microfinance and micro-entrepreneurship in Yemen. The study utilized a Quantitative research approach and convenience sampling with a self-administered survey using Structural question modelling (SEM) for data analysis. The respondents were customers of Islamic microfinance institutions (IMIFs) in Yemen. The sample of the study was 290 responses collected from Sana’a governorate. The outcomes of the study indicate that the micro-takaful and entrepreneurship training play as effective moderating and mediating factors between the Islamic microfinance and micro-entrepreneurship in Yemen. It also revealed that Microfinance has a significant and positive effect on Micro-Entrepreneurship. Moreover, the findings of the study therefore provide guidance for policy-makers and microfinance institutions as well as the microenterprises to avoid the operating risks and improve their business activities.